Tindak Pidana Pencurian Yang Dilakukan Residivis Dilihat Dari Aspek Penegakan Hukum - Sofyan Daud; Fence Wantu; Avelia Avelia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to determine law enforcement efforts for criminal acts of theft committed by recidivist perpetrators in the jurisdiction of the Gorontalo City Resort Police from the aspect of law enforcement. The research method used in this research is empirical research, using a document study approach, case studies, observations, interviews which are then analyzed qualitatively. The research results show that the analysis regarding law enforcement efforts against recidivists carried out by the Gorontalo City Police uses efforts; preventive, namely providing legal education to the community and repressive efforts in the form of bringing justice by carrying out investigations, arrests, investigations up to the court level. It can be concluded that this preventive effort is an outreach by providing understanding to the community so that they participate in overcoming the problem of crimes committed by a recidivist, especially in the family environment, school environment and repressive efforts in the form of taking firm action against a recidivist. The action in question is in the form of investigation, arrest. , investigation up to the court level, this action is the last action if pre-emptive action is not successful.